A multi-objective adaptive memetic algorithm and engineering application for a double-floor layout problem with separate human and vehicle transport elevators - Ji, Dan; Zhang, Zeqiang; Zhao, Minjie; He, Zongxing; Guo, Zihan (Engineering applications of artificial intelligence, 2025)
Planning the use and location of elevators is crucial in ensuring the safety and cost-efficiency of multi-floor workshop layouts. To this end, this study proposes a double-floor layout problem considering separate human and vehicle transport elevators. The constructed mixed-integer programming model analyzes flexible position constraints of elevators and different types of transport routes, intending to minimize employee movement and material handling costs. Subsequently, a multi-objective adaptive memory algorithm that includes a unique three-layer encoding and decoding strategy and adaptive local search is developed to solve this problem. Experimental results on three small-scale benchmark instances validate the accuracy of the proposed model and algorithm. Moreover, the developed algorithm obtains the Pareto frontier solution in all benchmark comparison experiments, indicating that it outperforms the other four competitive algorithms in the existing literature. Finally, the proposed separated elevator layout structure and intelligent algorithm are applied to a real-world reducer workshop containing 20 departments. The results demonstrate the superiority of the proposed layout under safety and low-cost conditions. •We study a double-floor layout problem with separated human and vehicle elevators.•A mathematical model is constructed to minimize human and material movement costs.•The problem is solved efficiently by a multi-objective adaptive memetic algorithm.•Comparison results of several algorithms verify the advantage of this algorithm.•The superiority of the proposed layout is proved in a real reducer workshop.